Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

“EVERYTHING ABOUT US IS FEMINIST”: The Significance of Ideology in Organizational Change - Thomas, Jan E. (Gender & Society, 1999)
This study explores the role feminist ideology played in long-term structural changes in feminist organizations. The vehicle for this exploration was a comparative case study of 14 feminist women's health centers that were started in the 1970s and were still in existence in the early 1990s. Drawing on interviews and site visits, the author describes the early collectivist structures, highlights some of the crises these organizations faced, and describes three structural ideal types that emerged in the 1990s. The analysis suggests three ideological issues that directed structural change: the importance of maintaining a system for the equitable distribution of power, the importance of growth versus autonomy, and the importance of feminism as an organizational outcome or internal process.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; organisations féministes; pratiques féministes; périodes historiques; recherche participative; régions géographiques; sciences humaines; structures organisationnelles; thématiques; travail social; états-unis; étude de cas